Evaluation of Hydrocarbon Saturation Using Carbon Oxygen (CO) Ratio and Sigma Tool - S. Alameedy, Usama (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
The main aim of this study is to evaluate the remaining oil in previously produced zones, locate the water productive zone and look for any bypassed oil behind casing in not previously perforated intervals. Initial water saturation was calculated from digitized open hole logs using a cut-off value of 10% for irreducible water saturation. The integrated analysis of the thermal capture cross section, Sigma and Carbon/oxygen ratio was conducted and summarized under well shut-in and flowing conditions. The logging pass zone run through sandstone Zubair formation at north Rumaila oil field. The zones where both the Sigma and the C/O analysis show high remaining oil saturation similar to the open hole oil saturation, could be good oil zones that do not appear to be water flooded. The zones where the Sigma analysis shows high residual oil saturation, which is close to open hole oil saturation and the C/O analysis, show medium residual oil saturation; this could indicate that these zones were fresh water flooded to a certain extent and they still keep some residual oil. If the C/O analysis shows low residual oil saturation, it indicates that these zones were probably fresh water flooded thoroughly. If both Sigma analysis and the C/O analysis show medium residual oil saturation, most probably these zones were saline water flooded to a certain extent and they still keep some residual oil.